Some Thoughts on Public Policy and Industrial Peace - Downie, Bryan (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1981)
This paper examines various strategies for industrial peace. Strategies which attack both the root causes of conflict and the effects of labour-management strife are discussed. The author then draws some broad inferences for public policy and for the parties in collective bargaining.